MENGAPA PERUSAHAAN MEMBAYAR DIVIDEN? - Budiarso, Novi S (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Dividend decisions, as determined by a firm’s dividend policy, are a type of financing decisions that affects the amount of earnings that a firm distributes to shareholders versus the amount of retains and reinvests. This paper examine the determinats of dividend payout of firms listed on Indonesian stock exchanges. Different variables related to the firms operations;  profitability, firm size, leverage and liquidity was analyzed on the dividend payouts of the firm. Using of 230 sample firms over the period 2010 to 2011, this study try to explore the dividend policy.  Regression logistic binary was applied to analysis the research questions.Results Show  that profitability, and firm size have significant relationship  with the  dividend  payout of the company, while leverage and liquidity have insignificant relationship with dividend payout. This indicate that in Indonesian stock exchange firm pay dividend based on their profit, the larger the firm the willing the firm to pay dividend.